Effects of Solution Mixing Temperature on Dielectric Properties of PMMA/Pristine Bentonite Nanocomposites - ESMER, KADİR (WILEY, 2014)
We examined the effects of mixing temperature on the dielectric properties of polymethylmethacrylate (PMMA)-pristine bentonite nanocomposites by using X-ray diffraction, FT-IR and dielectric spectroscopies. The samples were prepared during 8 hours at temperatures 265 K, 273 K, 281 K, 289 K and 298 K without any intercalative agent and the PMMA to pristine bentonite weight ratio was chosen as 1 : 10. It was observed that with decreasing the mixing temperatures, the permittivity decreases and the dielectric relaxation displaces towards the lower frequencies with the decrease of mixing temperatures. (c) 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39907.
Keywords: clay; dielectric properties; X-ray; MECHANICAL-PROPERTIES; MONTMORILLONITE CLAY; THERMAL-STABILITY; POLY(METHYL; POLYMERIZATION; INTERCALATION; OXIDE); BLEND